MOTIVASI WISATAWAN MILLENNIAL BERKUNJUNG KE DESA WISATA JATILUWIH KABUPATEN TABANAN - Andre Adi Putra Pratama, I Putu; Suardana, I Wayan; Dewi, LGLK. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 9 No 2 (2021): Jurnal IPTA (December 2021)DO - 10.24843/IPTA.2021.v09.i02.p03, 2021)
The millennial generation is a generation that is young and has more courage to travel in the new normal era compared to the generations above and below. Therefore, this study aims to determine the factors that influence the motivation of millennial tourists to visit Jatiluwih Tourism Village. This study uses descriptive quantitative data analysis with the confirmatory factor analysis method. The sampling technique was taken by purposive sampling with a total of 200 respondents from the millennial tourists who visited the Jatiluwih Tourism Village, Tabanan Regency. The data collection using observation, questionnaires, and interviews. The data analysis technique used factor analysis which was assisted by using SPSS Version 26 for Windows. Five push factors influence the motivation of millennial tourists to visit Jatiluwih Tourism Village, Tabanan Regency, namely: the desire to escape from routines, hobbies, enchant kinship and relationship, adventure, and prestige and four pull factors that influence the motivation of millennial tourists to visit Jatiluwih Tourism Village, Tabanan Regency, namely: natural places, sanitation facilities, cleanliness, and tourist attractions. The factor of desire escape from routine becomes the dominant factor in encouraging millennial tourist to visit the Jatiluwih Tourism Village, Tabanan Regency with an eigenvalue of 4,734 and percentage variance equal to (26.301%), while the factors natural places become the dominant factor in attracting millennial tourist to visit the Jatiluwih Tourism Village, Tabanan Regency, with an eigenvalue value of 7.478 and percentage of variance (33.989%).